A snapshot study on larval fish diversity in selected mangrove areas of Peninsular Malaysia, Malaysia / Izzati Adilah Azmir... [et al.] - Azmir, Izzati Adilah; Amin, Smn; Esa, Yuzine; Md Yasin, Ina-Salwany; Ara, Roushon (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The study on composition, abundance and diversity of larval fish was conducted with the aim to attain information on larval fish breeding ground and made easy for fishery management. Larval fish were collected during September 2015 from mangrove areas of Pekan Pahang, Pendas Johor, Matang Perak and Setiu Terengganu using a bongo net, towed at a depth of about 0.5 m from the surface for 5 min against the tidal flow. A total of 354 larval fish were collected, representing 21 families and 51 species. The top 3 families were Gobiidae (39.26%), Engraulidae (14.97%) and Clupeidae (14.40%), occurred in all sampling areas except in Setiu. The most abundant 11 species formed about 50% of all collected larval fish. Gobiidae spp. were the most abundant, making up 17.8% of the total catch, followed by Clupeidae spp. (12.7%), Engraulidae spp. (8.2%), Ambassis dusumieri (6.5%), Thryssa kammalensis (4.8%), Pseudogobius masago (both 4.8%), Sillaginidae spp. (4.2%), Ambassidae spp. (3.4%), Pseudogobius sp. (3.4%), Blenniidae spp. (2.8%), and Hemigobius hoevenii (2.5%). The highest diversity of larval fish was recorded for Pendas, Johor with Shannon Wiener index Hs = 2.699, and the lowest was Setiu, Terengganu (Hs = 0.832). The highest evenness index of larval fish species was recorded for Pekan, Pahang with Es = 0.815 and the lowest for Setiu Terengganu with Es = 0.465, indicating high single-species dominance. Species overlapping was the highest between Pendas and Setiu at 14.3%, and zero similarity of fish composition was recorded between Matang and Setiu according to Jaccard coefficient. Findings from surveillance of larval fish species provide valuable information for future biodiversity studies and allow better management of biodiversity resources in the mangrove ecosystem of Malaysia.